Successful management of auto knotted intravesical infant feeding tube by minimal invasive technique - Sidharth Khullar; Molay K Bera; Anup K Kundu; Dilip K Pal (Wolters Kluwer Medknow Publications, 2012)
We report a case of acute urinary retention due to intravesical auto knotting of infant feeding tube in a child treated successfully by endoscopic approach.